Fundamental questions in cross-cultural psychology - Vijver, Fonds J. R. van de; Chasiotis, Athanasios; Breugelmans, Seger M. (Cambridge University Press, 2011)
"Cross-cultural psychology has come of age as a scientific discipline, but how has it developed? The field has moved from exploratory studies, in which researchers were mainly interested in finding differences in psychological functioning without any clear expectation, to detailed hypothesis tests of theories of cross-cultural differences. This book takes stock of the large number of empirical studies conducted over the last decades to evaluate the current state of the field. Specialists from various domains provide an overview of their area, linking it to the fundamental questions of cross-cultural psychology such as how individuals and their cultures are linked, how the link evolves during development, and what the methodological challenges of the field are. This book will appeal to academic researchers and postgraduates interested in cross-cultural research"--Provided by publisher.